2018
DOI: 10.1159/000493739
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Orexinergic System on Survival in Septic Rats

Abstract: Background: The orexinergic (OXergic) system contributes to the defense system. It has also been reported that the degeneration of OXergic neurons occurs during sepsis. Thus, the decline of OXergic activity may contribute to impairment of the defense system in sepsis. In this study, we determined whether: (i) lipopolysaccharide (LPS) reduces the brain orexin A (OXA) content and (ii) the OXergic system contributes to survival from sepsis in rats. Methods: With approval of our protocol by our University Animal E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The OXergic neurons could degenerate by neuroinflammation with the decline of OXergic activity, which may partly characterize the symptoms of sepsis [ 12 ]. Indeed, we recently found that LPS significantly reduced OXA contents in the pons containing the locus coeruleus which may impair sympathetic nervous system [ 9 ]. Several reports [ 13 , 14 ] suggest that plasma OXA may reflect OXergic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OXergic neurons could degenerate by neuroinflammation with the decline of OXergic activity, which may partly characterize the symptoms of sepsis [ 12 ]. Indeed, we recently found that LPS significantly reduced OXA contents in the pons containing the locus coeruleus which may impair sympathetic nervous system [ 9 ]. Several reports [ 13 , 14 ] suggest that plasma OXA may reflect OXergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent animal studies showed that inflammation degenerate orexin (OX) neurons and reduce OXergic activity [ 6 8 ]. Indeed, we found that lipopolysaccharide (LPS) significantly reduces OXA content in the pons and there was a good correlation between OXA content in the pons and survival rate of rats [ 9 ]. We previously suggested that plasma OXA may reflect neuronal OXergic activity because of significant increases in plasma OXA at emergence from general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports indicate that LPS or TNFα (a major cytokine involved in septic shock) were also able to suppress orexin neuronal activity (159). More recently, the use of orexin-neuron ablated mouse model (OX/ataxin-3 transgenic mouse model) injected with LPS revealed a high mortality rate as compared to wild type mice (160). Moreover, the injection of LPS in wild type mice reduced OXA tissue content compared to untreated mice (160).…”
Section: Orexins In Diseasementioning
confidence: 99%
“…More recently, the use of orexin-neuron ablated mouse model (OX/ataxin-3 transgenic mouse model) injected with LPS revealed a high mortality rate as compared to wild type mice (160). Moreover, the injection of LPS in wild type mice reduced OXA tissue content compared to untreated mice (160). Yanagisawa's group had clearly shown that the subcutaneous diffusion of OXA using an osmotic pump in LPS-induced endotoxin shock mice improve the survival of these mice (77).…”
Section: Orexins In Diseasementioning
confidence: 99%